Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension